2022
DOI: 10.1371/journal.pone.0275033
|View full text |Cite
|
Sign up to set email alerts
|

Automatic multi-anatomical skull structure segmentation of cone-beam computed tomography scans using 3D UNETR

Abstract: The segmentation of medical and dental images is a fundamental step in automated clinical decision support systems. It supports the entire clinical workflow from diagnosis, therapy planning, intervention, and follow-up. In this paper, we propose a novel tool to accurately process a full-face segmentation in about 5 minutes that would otherwise require an average of 7h of manual work by experienced clinicians. This work focuses on the integration of the state-of-the-art UNEt TRansformers (UNETR) of the Medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 27 publications
(21 reference statements)
0
23
0
Order By: Relevance
“…Recently, fully automated image segmentation of the craniomaxillofacial bones from CBCT has been proposed [ 36 , 37 ]. These studies applied artificial intelligence, more specifically deep learning by neural networks, thereby eliminating the need of manual image segmentation and operator variability [ 36 , 37 ]. Artificial intelligence has been applied for automatic segmentation of the mandibular ramus and condyle [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, fully automated image segmentation of the craniomaxillofacial bones from CBCT has been proposed [ 36 , 37 ]. These studies applied artificial intelligence, more specifically deep learning by neural networks, thereby eliminating the need of manual image segmentation and operator variability [ 36 , 37 ]. Artificial intelligence has been applied for automatic segmentation of the mandibular ramus and condyle [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, automatic methods, such as computer-aided measurements and CT-based volumetric analysis, demonstrated higher accuracy and reliability compared with manual techniques. For example, Gillot et al 27 (2022) compared manual and automatic measurements of orbital fracture area using a 3-dimensional UNETR segmentation method on cone-beam CT scans and found that the automatic method showed higher accuracy and lower interobserver variability than the manual method. Inoue et al 28 (2022) developed an automated fracture screening method using an object detection algorithm on whole-body trauma CT, suggesting the potential advantages of automatic methods in detecting fractures with higher accuracy and reliability compared with manual techniques.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we evaluated the tooth movement of all lower teeth after correcting mild to moderate malocclusion, while the literature mainly reports different evaluations and methodologies, such as the levelling of only mandibular anterior teeth, 27 assessment of severe maxillary malocclusion, 6 evaluation of maxillary canine distalization, 14 en-masse retraction utilizing miniscrews, 35 transversal tooth movement of mandibular lateral segments, 15 second molar protraction and upper canine retraction. 36 The automated AI-based dental tools used in this study are accurate 8,[19][20][21][22][23][24]26,31,32 and facilitate the assessment and quantification of tooth movement, reducing the time needed by clinicians and researchers to analyse imaging processes and evaluations by at least 90%. It is important to note that while commercial companies such as Relu, 37 Diagnocat 38 and Materialise, 39 as well as previous studies, have demonstrated similar applications, most of their tools are not integrated into the same platform and are not easily accessible due to cost and code unavailability.…”
Section: Discussionmentioning
confidence: 99%
“…The image pre-processing included T1 CBCT orientation, 15 T2 registration, 29 as well as T1 and T2 IOS registration to the CBCT scans 30 with validated semi-automated tools (Figure 1) and completely automated tools (Figure 2). 8,[19][20][21][22][23][24]26,31,32 The T1 CBCTs orientation was performed positioning the mandibular 3D model as follows: The lower border of the mandible, mesial surface of first molars and midline were aligned, respectively, with the axial, coronal and sagittal axis. 15 Subsequently, the T2 CBCT images were manually approximated to the T1 images and a voxel-based registration was performed.…”
Section: Image Processingmentioning
confidence: 99%
See 1 more Smart Citation